Eksegesis Mazmur 73: Pergumulan Orang Benar Tentang Kemakmuran Orang Fasik - Samgar Setia Budhi (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2019)
The suffering of godly men and the prosperity of the wicked often become the struggle for faithful men. This issue has been around for all ages, from the biblical times until today. This struggle could have implications for the faith of the believers within one’s life. Therefore the sound understanding of God and His will through the scripture is needed. Psalm 73 is one of the Bible texts that is talking about this important issue. Through a pure biblical qualitative study with literal-grammatical-historical-contextual interpretation and exegesis theory approach, and also considering the literature style of the Psalm it is found that the base of the struggle from the existence of prosperity among the wicked is the problem from the heart. An envious heart toward the wealthiness of the wicked often moved the faith of the godly men about the kindness of the Lord. But when believers have an intimate relationship with the Lord, then new perspectives will be opened by God concerning the struggle. God is sovereign towards men’s life. The end of the wicked lives has been determined. On the contrary, for those who live in faith, the presence of God is the highest goodness because the life of a believer along with the Lord with him will always be under His nurture.Penderitaan orang benar dan kemakmuran orang fasik seringkali menjadi pergumulan bagi orang yang beriman. Isu ini sesungguhnya ada sepanjang zaman yaitu sejak zaman Alkitab hingga masa kini. Pergumulan ini dapat berimplikasi kepada iman orang percaya di tengah kehidupannya. Oleh sebab itu diperlukan pemahaman yang benar tentang Allah dan kehendak-Nya melalui kebenaran firman-Nya. Mazmur 73 adalah salah satu teks Alkitab yang membicarakan tentang isu penting ini. Melalui studi kualitatif kajian biblika murni dengan pendekatan teori tafsir literal-gramatikal-historikal-kontekstual dan eksegesis, serta dengan mempertimbangkan bentuk sastra dari Mazmur didapatkan pemahaman bahwa masalah hati merupakan dasar dari munculnya pergumulan tentang kemakmuran orang fasik. Hati yang cemburu terhadap kemakmuran orang fasik seringkali menggoyahkan keyakinan orang beriman akan kebaikan Allah. Tetapi ketika orang beriman memiliki persekutuan yang intim dengan Allah, maka ada perspektif baru yang akan dibukakan oleh Allah tentang pergumulannya. Sesungguhnya Allah berdaulat atas hidup manusia. Akhir hidup orang fasik sudah ditentukan. Tetapi bagi orang beriman, penyertaan Tuhan adalah kebaikan yang tertinggi karena dengan penyertaan Tuhan hidup orang beriman akan selalu dalam pemeliharaan-Nya.